KOMPOSISI GAMBAR PADA PROGRAM DOKUMENTER TELEVISI WANITA NUSANTARA EPISODE SANG PENARI MATAHARI JAWA - Tyas Arum Delimasari; Heriyanto Heriyanto (Institut Seni Indonesia Padangpanjang, 2022)
Women of the archipelago edition of the Javanese Sun Dancers is a program that provides information and education about the seblang dancer and its rituals with facts from sources. This documentary explains about how Susi as a woman who performs Banyuwangi culture. The ritual for 7 days in a row makes Susi have her own story. Susi's story that was not exposed by the public. In the creation of the production work of the television documentary Wanita Nusantara edition of the Javanese Sun Dancers, the writer as the director has completed the production more or less according to the plan. This program applies the composition of image framing and subject or object. With a framing approach: rule of thirds, looking room and head room. Of course, with variants of type of shot and camera angle. The application of image composition aims to make the images presented vary and produce a beautiful image, so that the information in this production work can be clearly explained and the audience's eye will continue to follow the existing image.